Deciphering the Mechanism of Inhibition of SERCA1a by Sarcolipin Using Molecular Simulations - Barbot, Thomas; Beswick, Veronica; Montigny, Cédric; Quiniou, Éric; Jamin, Nadège; Mouawad, Liliane (Frontiers in Molecular Biosciences, 2021)
SERCA1a is an ATPase calcium pump that transports Ca2+ from the cytoplasm to the sarco/endoplasmic reticulum lumen. Sarcolipin (SLN), a transmembrane peptide, regulates the activity of SERCA1a by decreasing its Ca2+ transport rate, but its mechanism of action is still not well understood. To decipher this mechanism, we have performed normal mode analysis in the all-atom model, with the SERCA1a-SLN complex, or the isolated SERCA1a, embedded in an explicit membrane. The comparison of the results allowed us to provide an explanation at the atomic level for the action of SLN that is in good agreement with experimental observations. In our analyses, the presence of SLN locally perturbs the TM6 transmembrane helix and as a consequence modifies the position of D800, one of the key metal-chelating residues. Additionally, it reduces the flexibility of the gating residues, V304 and E309 in TM4, at the entrance of the Ca2+ binding sites, which would decrease the affinity for Ca2+. Unexpectedly, SLN has also an effect on the ATP binding site more than 35 Å away, due to the straightening of TM5, a long helix considered as the spine of the protein. The straightening of TM5 modifies the structure of the P-N linker that sits above it, and which comprises the 351DKTG354 conserved motif, resulting in an increase of the distance between ATP and the phosphorylation site. As a consequence, the turn-over rate could be affected. All this gives SERCA1a the propensity to go toward a Ca2+ low-affinity E2-like state in the presence of SLN and toward a Ca2+ high-affinity E1-like state in the absence of SLN. In addition to a general mechanism of inhibition of SERCA1a regulatory peptides, this study also provides an insight into the conformational transition between the E2 and E1 states.